Quality improvement of mining specialists tarining on the basis of cooperation between Saint-Petersburg mining university and Orica company - M. N. Overchenko; M. A. Marinin; S. P. Mozer (Записки Горного института, 2017)
The analysis of practical solutions for a joint cooperation between the Mining University and the Australian company Orica resulted in the decision of creation a Competence center in the field of mining. The role of mining engineering and vocational education as necessary components of sustainable development of the territories was highlighted. The best Russian and international experience of collaboration between technical universities and main companies-players in the mining area is analyzed; an important role belongs to the involvement of regional executive authorities in a collaboration in the field of industrial safety. The prospects for the creation of a joint integration platform for a university and a company is considered on the example of creation of scientific educational laboratory of blasting technologies and modeling; the laboratory was opened under the agreement between Saint-Petersburg mining university and Orica company with the purpose of improvement of mining engineers training in the field of blasting operations, the development of scientific and research investigation activities, the organization of professional retraining and upgrade qualifications of specialists of mining area. A set of target indicators of the effectiveness of the scientific educational laboratory performance are given, as well as a general evaluation of the cooperation project efficiency.